2007
DOI: 10.1093/ageing/afm118
|View full text |Cite
|
Sign up to set email alerts
|

START (screening tool to alert doctors to the right treatment) an evidence-based screening tool to detect prescribing omissions in elderly patients

Abstract: Background inappropriate prescribing encompasses acts of commission i.e. giving drugs that are contraindicated or unsuitable, and acts of omission i.e. failure to prescribe drugs when indicated due to ignorance of evidence base or other irrational basis e.g. ageism. There are considerable published data on the prevalence of inappropriate prescribing; however, there are no recent published data on the prevalence of acts of omission. The aim of this study was to calculate the prevalence of acts of prescribing om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
237
4
16

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(274 citation statements)
references
References 17 publications
(14 reference statements)
14
237
4
16
Order By: Relevance
“…General prescribing criteria for older adults do not specifically consider the particularities of a progressive, life‐limiting nature of dementia 45, 46, 47, 48, 49. We anticipated that this project would generate a list of appropriate and inappropriate medications for managing co‐morbidities in dementia, similar to other existing explicit prescribing criteria in older people such as the Beers and STOPP/START criteria 60, 61.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…General prescribing criteria for older adults do not specifically consider the particularities of a progressive, life‐limiting nature of dementia 45, 46, 47, 48, 49. We anticipated that this project would generate a list of appropriate and inappropriate medications for managing co‐morbidities in dementia, similar to other existing explicit prescribing criteria in older people such as the Beers and STOPP/START criteria 60, 61.…”
Section: Discussionmentioning
confidence: 99%
“…Medication management decisions for people with dementia are often based on data collected in younger adults or peers, which may not be generalisable or relevant to this population. The existing explicit prescribing criteria developed for older people do not account for the additional complexities of dementia or its life‐limiting nature 45, 46, 47, 48, 49. Consensus‐based guidance specifically for people with dementia would assist clinicians with decision‐making in this population 50, 51.…”
Section: Introductionmentioning
confidence: 99%
“…A follow-up study using the STOPP criteria found at least one PIM among the regular prescriptions of 35% of acutely hospitalized elderly patients [21]. A PPO rate of 57.9% was identified using the START criteria in a similar hospitalized elderly population [22]. Elderly patients admitted to hospital are generally sicker and frailer than elderly patients reviewed in primary care, and the prevalence rates for IP and PPOs among elderly patients obtained in these Irish hospital studies do not reflect the Irish population as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…The START (Screening Tool to Alert doctors to Right Treatment) criteria are a new tool in screening for PPOs in the elderly population, and the published results indicate a very high prevalence, between 51 and 72% of patients [13,15].…”
Section: Introductionmentioning
confidence: 99%